Influence of Right Ventricular Dysfunction on Outcomes of Left Ventricular Non-compaction Cardiomyopathy - Wang, Wuwan; Chen, Wei; Lin, Xue; Fang, Ligang (Frontiers in Cardiovascular Medicine, 2022)
Background: Various adverse outcomes such as mortality and rehospitalization are associated with left ventricular non-compaction (LVNC). Due to data limitations, prospective risk assessment for LVNC remains challenging. This study aimed to investigate the influence of right ventricular (RV) dysfunction on the clinical outcomes of patients with LVNC through accurate and comprehensive measurements of RV function. Methods and Results: Overall, 117 patients with LVNC (47.6±18.3 years, 34.2% male) were enrolled, including 53 (45.3%) and 64 (54.7%) patients with and without RV dysfunction, respectively. RV dysfunction was defined as meeting any two of the following criteria: (i) tricuspid annular systolic excursions < 17 mm, (ii) tricuspid S’ velocity < 10 cm/s, and (iii) RV fractional area change < 35%. RV dysfunction was significantly higher in patients with biventricular involvement than in those with LV involvement only (2=6.213, P=0.013). After a follow-up period of 69.0 [33.5, 96.0] months, 18 (15.4%) patients reached the primary endpoint (all-cause mortality), with 14 (26.4%) and 4 (6.3%) from the RV dysfunction group and normal RV function group, respectively. The Kaplan–Meier method and log-rank test revealed that patients with RV dysfunction had a higher risk of all-cause mortality than those in the control group (hazard ratio [HR]: 5.132[2.003, 13.15], p=0.0013). Similar results were obtained for patients with left ventricular ejection fraction (LVEF) < 50% [HR, 6.582; 95% confidence interval (CI), 2.045–21.19; p=0.0367]. The relationship between RV dysfunction and heart failure rehospitalization and implantation of implantable cardioverter-defibrillator/cardiac resynchronization therapy was not statistically significant (both p>0.05). The multivariable Cox proportional hazard modelling analysis showed that RV dysfunction (HR: 4.950 [1.378, 17.783], p=0.014) and impaired RV global longitudinal strain (HR: 1.103 [1.004, 1.212], p=0.041) were independent predictors of mortality rather than increased RV end-diastolic area and decreased LV ejection fraction (both p>0.05). Conclusions: RV dysfunction is associated with the prognosis of patients with LVNC.